A Hierarchical Control Scheme for Smooth Transitions between Level Ground and Ramps with a Robotic Transtibial Prosthesis - Yuan, Kebin; Wang, Qining; Zhu, Jinying; Wang, Long (IFAC Proceedings Volumes, 2014)
This paper presents a hierarchical control scheme for a robotic transtibial prosthesis to realize smooth locomotion transitions between level ground and ramps. The high level controller identifies current terrain with a fuzzy logic based method and decides the corresponding parameters for lower level controllers. The middle level controller detects different gait phases of one gait cycle on a specific terrain and decides which control method to be used for the current phase. Based on the identified terrain and gait phase, the low level controller performs damping control for controlled plantarflexion/dorsiflexion, and angle control for the swing phase. To evaluate the effectiveness of the proposed control scheme, we design and construct a robotic transtibial prosthesis prototype. Experimental results on normalized stance time, normalized peak ground reaction force, and center of pressure shift in anterior/posterior show improved gait symmetry and walking stability of an amputee subject on ramps with the proposed control scheme. A 17-s long trial that includes different terrains and terrain transitions indicates that the proposed scheme can realize smooth locomotion transitions between level ground and ramps.